2021
DOI: 10.1186/s12955-021-01801-0
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric patients’ reasons for visiting dentists in all WHO regions

Abstract: Background Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact are the four oral health-related quality of life (OHRQoL) dimensions (4D) or areas in which oral disorders impact pediatric patients. Using their dentists' assessment, the study aimed to evaluate whether pediatric dental patients' oral health concerns fit into the 4D of the Oral Health-Related Quality of Life (OHRQoL) construct. Methods Dentists who treat childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Because dPROMs capture what matters to patients, their common measurement targets should be related to the reasons why patients seek treatment for their oral health problems. An international study conducted in all six World Health Organization health regions corroborated this [37]. This study found that Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact capture dental patients' perceived impact of oral health problems worldwide, regardless of whether the patient currently suffers from oral diseases or intends to prevent them in the future [3].…”
Section: Comparison With Literaturesupporting
confidence: 55%
See 3 more Smart Citations
“…Because dPROMs capture what matters to patients, their common measurement targets should be related to the reasons why patients seek treatment for their oral health problems. An international study conducted in all six World Health Organization health regions corroborated this [37]. This study found that Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact capture dental patients' perceived impact of oral health problems worldwide, regardless of whether the patient currently suffers from oral diseases or intends to prevent them in the future [3].…”
Section: Comparison With Literaturesupporting
confidence: 55%
“…This study found that Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact capture dental patients' perceived impact of oral health problems worldwide, regardless of whether the patient currently suffers from oral diseases or intends to prevent them in the future [3]. While these findings applied to all dental patients, a subsequent analysis restricted to pediatric dental patients confirmed these results [37].…”
Section: Comparison With Literaturementioning
confidence: 53%
See 2 more Smart Citations
“…Modifying factors might be disease such as eating disorders (bulimia) or caries, facial trauma, or physiological ageing processes such as sarcopenia of the masticatory muscles.Figure redrawn from Ref. 1 under Creative Commons Licence (CC BY 3.0)In the overall context of oral health-related quality of life, orofacial frailty or oro-facial hypofunction should also take into account factors that relate to the domains oral function, oro-facial pain, oro-facial appearance and psychosocial impact, as they relate to the reasons as to why patients seek help from dental and medical professionals 41. Oro-facial function in the context of ageing The world's population continues to grow and to live longer.…”
mentioning
confidence: 99%